OPTIMALISASI PENGELOLAAN ZAKAT PRODUKTIF UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT PADA BAZNAS KABUPATEN SOPPENG - Nurwahidah; Kasjim Salenda; Asni (Universitas Islam Negeri Alauddin Makassar, 2024)
The main issue in this study is how to optimize the management of productive zakat for the economic empowerment of the community in BAZNAS Soppeng Regency. This study is a field research with a qualitative approach, using documentation and interviews as data collection methods. The results of the study show that the zakat management mechanism in BAZNAS Soppeng Regency consists of several stages, including: planning, organizing, and implementing the collection of zakat funds from muzakki to be distributed to mustahik. Additionally, the distribution and use of zakat consists of two types of assistance: consumptive assistance and productive assistance. The challenges faced by BAZNAS Soppeng Regency in its efforts to improve the economy of the poor community include the lack of strict sanctions in the Zakat Management Law, limited funds, and low zakat awareness among muzakki. The efforts made by BAZNAS Soppeng Regency include the establishment of Zakat Collection Units (UPZ), providing convenience for muzakki, and distributing zakat in cash. The benefits of the productive zakat assistance received by mustahik from BAZNAS Soppeng Regency include an increase in income, although the profit gained is not significant and is mostly used for daily living expenses.